Evidences in the treatment of idiopathic normal pressure hydrocephalus - Oliveira,Matheus Fernandes de (2015)
Summary Introduction: idiopathic normal pressure hydrocephalus (INPH) is characterized by gait apraxia, cognitive dysfunction and urinary incontinence. There are two main treatment options: ventriculoperitoneal shunt (VPS) and endoscopic third ventriculostomy (ETV). However, there are doubts about which modality is superior and what type of valve should be applied. We are summarizing the current evidence in INPH treatment. Methods: an electronic search of the literature was conducted on the Medline, Embase, Scielo and Lilacs databases from 1966 to the present to obtain data published about INPH treatment. Results: the treatment is based on three pillars: conservative, ETV and VPS. The conservative option has fallen into disuse after various studies showing good results after surgical intervention. ETV is an acceptable mode of treatment, but the superiority of VPS has made the latter the gold standard. Conclusion: well-designed studies with a high level of appropriate evidence are still scarce, but the current gold standard for treatment of INPH is conducted using VPS.